Integrated proportional-integral control for enhanced grid synchronization and power quality in photovoltaic-electric vehicle systems - Mahalakshmi, V. G.; Gopala Reddy, K.; Shakunthala, C. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Photovoltaic (PV)-grid with electrical vehicle penetration introduces harmonics to the main power system. This paper explores the disturbances introduced due to both PV and electric vehicles (EVs) in the grid. PV acting as the source and EV acting as both the load and the source introduces harmonics to the main grid. The combined harmonics from both the PV and EV are controlled using the integrated DQ controller on the voltage source converter (VSC) that connects to the grid from the PV source. The real and reactive power is controlled in a decoupled manner to obtain better control of the harmonic reduction introduced in the grid. This study investigates the use of proportional-integral (PI) control techniques to develop an integrated controller that can effectively handle both PV synchronization and power quality when using electric vehicles. To reduce harmonics in the grid current, the study combines multicarrier space vector pulse width modulation (SVPWM) with PI control on the grid-connected converter through a dual-control loop system devoted to PV grid synchronization, with one loop specifically addressing EV battery charging control. DQ method yields a total harmonic distortion (THD) of 2.74% for voltage and 3.44% for current according to the IEEE 519 standards.